The Effectiveness of Puppet Theater in Developing the Linguistic Abilities of Third Primary Students - Yaghi, Asma'a Abdel-Mutie (Journal of Educational and Psychological Sciences, 2020)
The effectiveness of the puppet theater in developing the abilities of third-grade primary students linguistically Summary. This study aimed to know the effectiveness of the Puppet Theater (puppet theater) to develop linguistically the capabilities of third primary students. The researcher used the experimental approach, the study sample consisted of third primary students (50) male and female students, and the study showed the following results: Identifying the effectiveness of teaching through the puppet theater in developing Arabic language skills (reading, writing, speaking, listening) at Third grade students, there are statistically significant differences at the level between the mean levels of the control group and the experimental group in the measurement (pre and post) of the total score for language skills tests that are attributed to the effectiveness of teaching through the puppet theater, achieving a high degree of effectiveness in teaching by theater (puppet) method To enable students to have four Arabic language skills. There are also statistically significant differences at a level between the arithmetic mean for the experimental group and the control group in developing Arabic language skills (reading, writing, speaking, and listening) and they were in favor of the experimental group. The researcher recommended the following: The need for vocational preparation for some basic education teachers through holding training courses on work and school theater performance and how to communicate and deal with that, because the lack of a competent teacher leads to a failure of theater activity. And the need to allocate hours in the educational curriculum for the theater on a weekly basis, to least two hours. Requesting the competent authorities to include theater education in school curricula.